Blended Learning as a Catalyst for Boosting University Students' Learning Motivation - Novita Sari Pohan; Almasdi Syahza; Suarman Suarman (STAI Hubbulwathan Duri, 2025)
In the digital era, enhancing the quality of education demands innovative approaches. Blended learning—combining face-to-face and online instruction—has emerged as a promising model to boost students’ learning motivation. This study employed a quantitative descriptive design to evaluate the effectiveness of blended learning in improving student motivation at UIN Suska Riau. Data were collected through questionnaires and observations. The population consisted of all students enrolled in the Economic Education Study Program, with a sample size of 143 respondents. The data were analyzed using descriptive statistics and inferential tests, including normality, homogeneity, and paired sample t-tests. Findings revealed a significant improvement in students’ learning motivation after the implementation of blended learning. The pretest results showed an average motivation score of 38.23, categorized as moderate. After blended learning was applied, the posttest average rose to 52.05, indicating a high level of motivation. A paired sample t-test yielded a p-value of 0.000 ( 0.05), confirming a statistically significant difference between pretest and posttest motivation levels. The results demonstrate that blended learning significantly enhances student motivation. These findings suggest that integrating blended learning can be an effective strategy for educators aiming to foster motivation and engagement. This study provides practical insights for lecturers and educational institutions seeking to adopt innovative learning models and develop more dynamic instructional strategies.